Quantifying and addressing the impact of measurement error in network models. (October 2022) - de Ron, Jill; Robinaugh, Donald J.; Fried, Eiko I.; Pedrelli, Paola; Jain, Felipe A.; Mischoulon, David; Epskamp, Sacha
Abstract: Network psychometric models are often estimated using a single indicator for each node in the network, thus failing to consider potential measurement error. In this study, we investigate the impact of measurement error on cross-sectional network models. First, we conduct a simulation study to evaluate the performance of models based on single indicators as well as models that utilize information from multiple indicators per node, including average scores, factor scores, and latent variables. Our results demonstrate that measurement error impairs the reliability and performance of network models, especially when using single indicators. The reliability and performance of network models improves substantially with increasing sample size and when using methods that combine information from multiple indicators per node. Second, we use empirical data from the STAR*D trial (n = 3, 731) to further evaluate the impact of measurement error. In the STAR*D trial, depression symptoms were assessed via three questionnaires, providing multiple indicators per symptom. Consistent with our simulation results, we find that when using sub-samples of this dataset, the discrepancy between the three single-indicator networks (one network per questionnaire) diminishes with increasing sample size. Together, our simulated and empirical findings provide evidence that measurement error can hinder network estimation when working with smaller samples and offers guidance on methods to mitigate measurement error. Highlights: Many psychological network studies use one item to query a symptom. One item variables are a major potential limitation for the reliability for networks due to measurement error. Here, we investigate the impact of measurement error on cross-sectional network models. We also investigate which different multiple-indicator methods can best be used to mitigate the effects of measurement error.